The relationship of yoga modified Melayu Deli music with anxiety in pregnant women at the Clinic Pratama Doa Ibu - Elsarika Damanik; Christina Roos Etty; Rizka Yohanna Fitri (Institute of Computer Science (IOCS), 2023)
Anxiety that occurs continuously in mothers, especially in the third trimester, can have a negative impact on the mother and fetus, both during and after childbirth. Where the impact of anxiety can affect the well-being of the fetus in the womb with breast milk increasing the risk of LBW (Low Birth Weight) and premature birth. Traditional music played with regular yoga movements has a good effect on stimulating fetal development. Can cause a positive response from the baby in the womb. The purpose of the study was to determine the relationship of Yoga Modification of Deli Malay Music with Anxiety in Pregnant Women at the Pratama Doa Ibu Clinic. The type of research used is Quasi Experiment with One Group Time Series Design approach. This research was conducted by the Doa Pratma Mother Clinic. The sample in this study were second and third trimester pregnant women with accidental sampling with a sample size of 32 respondents. The results showed that there was a relationship between Yoga Modification of Deli Malay Music with Anxiety in Pregnant Women at the Doa Ibu Pratama Clinic with a p value (0.000) <0.05. From the conclusion, it is found that there is a relationship between Yoga Modification of Malay Deli Music with Anxiety in Second and Third Trimester Pregnant Women at the Doa Ibu Primary Clinic in 2022.